Web-Based Library Service Information System Design Using Electronic Customer Relationship Management (E-CRM) At SMK YUPPENTEK 1 Tangerang - Ita Erliyani Ita Erliyani; Widya Safitri; Tobi Nurhidayat (CCIT Journal, 2022)
The utilization of information and communication technology in education is a means of informing quality education. One area that feels the impact of technology in the library. SMK Yuppentek 1 Tangerang currently has a library, but it is not computerized with an information system. In other words, all data is still written in a ledger to recapitulate the transactions that occur so that the data is less accurate in the reporting process. The collection of books that is continually increasing in the library is not followed by the readiness of the officers to update the data so that it becomes difficult for visitors to get the latest information. This study aims to create a website-based library information system at SMK Yuppentek 1 Tangerang city by using Electronic Customer Relationship Management (E-CRM) as a service improvement strategy that is oriented to the needs of members so that it becomes a solution for processing library information data to be practical, accurate and effective. Easy and excellent service can be obtained by visitors well. The methodology of this research analysis is the method of data collection and analysis of Performance, Information, Economic, Control, Efficiency, Service (PIECES), which will present a discussion of the theoretical basis, stages of analyzing and modeling processing systems using Unified Modeling Language (UML), black-box testing that will be used as a testing method.